Answer:
- (x -3)(x+3)(2x +1)
- (x -1)(x +1)(x +3)
- (2x -1)(2x +1)(x -4)
Step-by-step explanation:
A) 2x³ +x² -18x -9 = x²(2x +1) -9(2x +1) = (x² -9)(2x +1) = (x -3)(x+3)(2x +1)
__
B) x³ +3x² -x -3 = x²(x +3) -1(x +3) = (x² -1)(x +3) = (x -1)(x +1)(x +3)
__
C) 4x³ -16x² -x +4 = 4x²(x -4) -1(x -4) = (4x² -1)(x -4) = (2x -1)(2x +1)(x -4)
_____
In each case, the third-level factoring mentioned in step 4 is the factoring of the difference of squares: a² -b² = (a -b)(a +b).
_____
The step-by-step is exactly what you need to do. It is simply a matter of following those instructions. You do have to be able to recognize the common factors of a pair of terms. That will be the GCF of the numbers and the least powers of the common variables.
Answer:
y = -3x -9
Step-by-step explanation:
slope = 1/3
perpendicular slope = -3
y = mx + b
0 = -3(-3) + b
-9 = b
y = -3x -9
Answer:
2x - 6
Step-by-step explanation:
2(3 - x) - 12 + 4x =
6 - 2x - 12 + 4x =
-6 + 2x =
2x - 6
No one wants to date you or anyone else because this is a Q&A app for homework, Quizs, and Classwork.
......................... 1/2